The employees and shareholders pressure on environmental accounting reporting practice in small and medium enterprises: evidence from China - Sulaiman Tahajuddin; Zhao Xin; Nur Shahida Ab Fatah (Universiti Malaysia Sabah, 2020)
The small and medium enterprises (SMEs) in China have achieved rapid and sustainable growth for more than three decades. Such growth has increasingly contributed to China's economic development. Yet, the public's sensitivity to environmental issues is increasingly demanding more research to be conducted on environmental topics. Therefore, the objective of this study is to examine the pressure of internal stakeholders, namely shareholders and employees of SMEs in Shanxi Province in China towards the need to comply with environmental accounting reporting. One hundred and fifty copies of questionnaires were distributed; one hundred twenty-nine ready copies were subsequently collected. The data were then analyzed by utilizing Partial Least Squares-Structural Equation Modeling (PLS-SEM) using SmartPLS 3.2.9. The results showed that employees of SMEs in Shanxi Province in China were able to pressure their employers to implement environmental accounting reporting. The insights of this study prove that employees of SMEs in Shanxi Province were serious on environmental issues as environmental accounting reporting can improve SMEs performances concerning the environment, inventory and controlling costs, more efficient technologies with less pollution, non-polluting products, etc.